Effects of levobupivacaine and bupivacaine on intracellular calcium signaling in cultured rat dorsal root ganglion neurons - Ozcan, Mete; Ayar, Ahmet; Alcin, Ergul; Ozcan, Sibel; Kutlu, Selim (Taylor & Francis Ltd, 2010)
Bupivacaine and levobupivacaine have been shown to be effective in the treatment of pain as local anesthetics, although the mechanisms mediating their antinociceptive actions are still not well understood. The aim of this study was to investigate the effects of bupivacaine and levobupivacaine on intracellular calcium ([Ca
Keywords: Local-Anesthetics; Molecular-Mechanisms; Neuropathic Pain; Sensory Neurons; Sodium-Channels; Currents; Gabapentin; Block; Ropivacaine; Enantiomers